Clostridium butyricum Ameliorates Atherosclerosis by Regulating Host Linoleic Acid Metabolism - Chao Yin; Peizhi Fan; Xiangyu Mou; Wenjing Zhao (Microorganisms)
Dysbiosis of the gut microbiota is strongly implicated in atherosclerosis (AS), thus prompting microbial modulation to be explored as a therapeutic strategy. However, limited evidence exists for probiotic interventions capable of alleviating AS. Here, we focused on Clostridium butyricum (C. butyricum; CB), a probiotic known for its production of short-chain fatty acids (SCFAs). We found that administration of C. butyricum to high-fat diet (HFD)-fed Apoe deficient (Apoe−/−) mice reduced plaque area by improving blood lipid profiles, decreasing macrophage infiltration in the aortic roots, and lowering the levels of circulating pro-inflammatory monocytes and macrophages. By non-targeted serum metabolomics analysis, C. butyricum treatment significantly reduced the levels of both linoleic acid and its downstream metabolites. Collectively, these findings establish C. butyricum-mediated amelioration of AS through modulation of linoleic acid metabolism.